Discovery of the Australian diving beetle Neobidessodes mjobergi (Zimmermann, 1922) in New Guinea (Coleoptera, Dytiscidae, Hydroporinae) - Suriani Surbakti; Michael Balke; Lars Hendrich (Check List, 2021)
The diving beetle genus Neobidessodes Hendrich & Balke, 2009 contains 10 species. Nine of them were considered endemic to Australia, one of them to the Trans Fly Savanna and Grasslands Ecoregion of New Guinea island. Here, we provide the first report of one of the Australian species, Neobidessodes mjobergi (Zimmermann, 1922), from the same region of New Guinea. We suggest that more focused research will reveal the occurrence of far more Australian diving beetle species in that region of New Guinea.